Merit System Implementation in the Government of Pekanbaru, Riau - Andarwati, Desi; Andri, Seno; Karneli, Okta; Adianto, Adianto (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to explore the implementation of the merit system in the Pekanbaru City Government using qualitative research methods. The findings indicate that the implementation of the merit system is characterized by both progress and challenges. While the system intends to modernize civil service management by focusing on qualifications, competencies, and performance, there are still significant areas for improvement. Although the civil service management system (SIMPEG) in Pekanbaru can process real-time data, it is not fully integrated with performance assessments, disciplinary actions, or career development processes. The e-performance system remains isolated, complicating the integration of personnel data for benefits and career growth. Furthermore, electronic documentation services are only partially digitized, and there is inadequate integration with the National Personnel Information System (SIMPEGNAS) managed by BKN. The planning and development of SIMPEG are ongoing, with many plans being short-term and incomplete. Addressing these issues requires a more comprehensive and long-term strategy, along with the establishment of technical policies to guide SIMPEG integration. Overcoming these challenges is crucial for enhancing civil service management and achieving improved governance and public service outcomes.